2016
DOI: 10.1371/journal.pone.0152913
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Placebo Controlled Trial of Ibuprofen for Respiratory Syncytial Virus Infection in a Bovine Model

Abstract: BackgroundRespiratory syncytial virus (RSV) is the most common cause of bronchiolitis and hospital admission in infants. An analogous disease occurs in cattle and costs US agriculture a billion dollars a year. RSV causes much of its morbidity indirectly via adverse effects of the host response to the virus. RSV is accompanied by elevated prostaglandin E2 (PGE2) which is followed by neutrophil led inflammation in the lung. Ibuprofen is a prototypical non-steroidal anti-inflammatory drug that decreases PGE2 leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 60 publications
(59 reference statements)
4
28
0
Order By: Relevance
“…[45,46] Steroids and NSAIDs increase viral shedding but have either null or beneficial effects on various clinical outcomes such as mortality, need for hospitalization, respiratory distress, and subsequent recurrent wheezing. [22,30,[47][48][49] We observed that NSAIDs and FPI when started on day 5 as monotherapy had almost identical clinical scores despite diverging viral loads, +174, (95% CI -303, +651) in ibuprofen monotherapy started on day 5 group) and -146, (95% CI -631, +340) in FPI monotherapy started on day 5 group.…”
Section: Plos Onementioning
confidence: 70%
See 4 more Smart Citations
“…[45,46] Steroids and NSAIDs increase viral shedding but have either null or beneficial effects on various clinical outcomes such as mortality, need for hospitalization, respiratory distress, and subsequent recurrent wheezing. [22,30,[47][48][49] We observed that NSAIDs and FPI when started on day 5 as monotherapy had almost identical clinical scores despite diverging viral loads, +174, (95% CI -303, +651) in ibuprofen monotherapy started on day 5 group) and -146, (95% CI -631, +340) in FPI monotherapy started on day 5 group.…”
Section: Plos Onementioning
confidence: 70%
“…This was useful only as proof of concept because infected but asymptomatic patients (human or bovine) will not often be diagnosable. [22] We have advanced current knowledge (1) by determining that initiation of treatment up to five days after inoculation is beneficial and (2) by demonstrating that dual therapy of an NSAID with an FPI should be used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations